Review; Efficacy of remineralization agents in arresting and reversing early carious lesions - Ahmad Jammah Algrny; Dr. Muhannad Salem Alharbi; Dr. Meshaal Abdullah Badi; Dr. Hibah Saad Al-Ahmadi; Dr. Shahad Abdurahman Sagaf; Dr. Mohammed Lugman Alsunari; Manee Ahmed Alghamdi; Abdullah Ahmed Alghamdi; Abdulmalik Saleh AlGhamdi; Dr. Khalid Omar Baeshin; Dr. Farid Naser Ashi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Dental caries is the most widespread chronic illness among children and adults globally, continuing to be the primary concern in dentistry. Dental caries is a complex, non-communicable illness characterized by biofilm mediation and dietary influence, leading to the net mineral loss of dental hard tissues. The contemporary understanding of caries development is founded on the repeated cycles of demineralization and remineralization, triggered by acidogenic bacteria inside the oral microenvironment. Dental remineralization is the process of depositing calcium and phosphate ions into the crystal gaps of demineralized enamel, resulting in a net mineral gain and inhibiting the advancement of early enamel diseases. The objective of the review was to qualitatively and quantitatively assess the remineralizing efficacy of various current treatments on simulated enamel defects arresting and reversing early carious lesions.